Intensity of mycophenolate mofetil treatment is associated with an impaired immune response to SARS‐CoV‐2 vaccination in kidney transplant recipients. Issue 2 (1st November 2021) - Kantauskaite, Marta; Müller, Lisa; Kolb, Thilo; Fischer, Svenja; Hillebrandt, Jonas; Ivens, Katrin; Andree, Marcel; Luedde, Tom; Orth, Hans M.; Adams, Ortwin; Schaal, Heiner; Schmidt, Claudia; et al.
Abstract : Kidney transplant recipients (KTRs) are extremely vulnerable to SARS‐CoV‐2 infection and show an impaired immune response to SARS‐CoV‐2 vaccination. We analyzed factors related to vaccination efficiency in KTRs. In a multicenter prospective observational study (NCT04743947), IgG antibodies levels against SARS‐CoV‐2 spike S1 subunit and their neutralization capacity after SARS‐CoV‐2 vaccination were analyzed in 225 KTRs and compared to 176 controls. After the vaccination, 56 (24.9%) KTRs became seropositive of whom 68% had neutralizing antibodies. This immune response was significantly lower compared to controls (239 [78–519] BAU/ml versus 1826 [560–3180] BAU/ml for KTRs and controls, p < .0001). The strongest predictor for an impaired response was mycophenolate mofetil (MMF) treatment. Multivariate regression analysis revealed that MMF‐free regimen was highly associated with seroconversion (OR 13.25, 95% CI 3.22–54.6; p < .001). In contrast, other immunosuppressive drugs had no significant influence. 187 out of 225 KTRs were treated with MMF of whom 26 (13.9%) developed antibodies. 23 of these seropositive KTRs had a daily MMF dose ≤1 g. Furthermore, higher trough MMF concentrations correlated with lower antibody titers (R −0.354, p < .001) supporting a dose‐dependent unfavorable effect of MMF. Our data indicate that MMF dose modification could lead to an improved immune response. Abstract : The study examines the dose dependent negative effect of mycophenolate mofetil on the observed poor immune response to COVID‐19 vaccination in kidney transplant recipients.